Chromosomal microarray in prenatal diagnosis - replacing traditional karyotyping - Winther, Alise Marie (UiT Norges arktiske universitet, 2019)
Abstract Background: In prenatal diagnosis, chromosomal microarray analysis (CMA) has not yet fully replaced conventional karyotyping. As CMA is able to detect smaller genomic imbalances compared to conventional karyotyping, it has become the first-tier test in pregnancies with ultrasound abnormalities. Objectives/aims: The aim of the study was to learn about CMA and its appliance in invasive prenatal testing and evaluate the findings in a selected pregnant population. We intended to discuss diagnostic yield using quantitative fluorescence polymerase chain reaction (QF-PCR) prior to CMA instead of QF-PCR and karyotyping. Methods: Data was collected at the University hospital of North Norway Department of Medical Genetics. The sample comprised 85 women aged 19 – 45 years (M=33.12, SD=6.6). Between December 2015 and august 2017, QF-PCR and karyotyping were performed in n=43 fetuses from women aged 19 - 44 (M=34.3, SD=6.4). Between September 2017 and December 2018 QF-PCR and CMA were performed in 41 fetuses from women aged 19 – 45 years (M=31.8, SD=6.7). Results: In the Karyotyping group, 18.6 % of the fetuses had a results of clinical importance (trisomy, monosomy and mosaic trisomy). In the CMA group, 24.3 % of the patients had a copy number variant (CNV) which were either pathogenic (class 5), likely pathogenic (class 4)or a variant of uncertain significance (VOUS). Only a small fraction (4,8%) of the CNVs in the CMA group were classified as class 4-5 and reported to the patients. Only one of these CNVs would have been detected by karyotyping and only one was detected by QF-PCR. Conclusion: As the purpose of this thesis was to learn about CMA and its role in invasive prenatal testing and evaluate the findings; we found CNVs that would not have been detected using karyotyping alone in the CMA group. Supporting the literature describing benefits for changing the invasive testing methods. However, findings of uncertain clinical significance challenge the genetic counselling. Therefore, a national collection of data ...